An assessment of calophyllum inophyllum biodiesel fuelled diesel engine characteristics using novel antioxidant additives. (15th September 2017) - Ashok, B.; Nanthagopal, K.; Jeevanantham, A.K.; Bhowmick, Pathikrit; Malhotra, Dhruv; Agarwal, Pranjal
Graphical abstract: Highlights: A novel antioxidant Ethanox was used for the present investigation. Effect of two antioxidants on biodiesel fuelled engine characteristics were studied. Brake thermal efficiency increased by 5.3% for Ethanox 1000 ppm with biodiesel. 21% reduction in oxides of nitrogen for Butylated hydroxytoluene 500 ppm addition. Higher hydrocarbon and smoke emissions were observed for all treated fuels. Abstract: In this present study, the effect of antioxidant additives with pure Calophyllum inophyllum methyl ester on the performance, combustion and emission characteristics has been investigated. New antioxidant additive namely Ethanox was added to the Calophyllum inophyllum biodiesel at concentrations of 200 ppm, 500 ppm and 1000 ppm for oxides of nitrogen reductions and the experimental results were compared to Butylated hydroxytoluene antioxidant at same concentrations. An experimental study was done on a twin cylinder, four stroke diesel engine at a constant speed of 1500 rpm with two different antioxidants, Ethanox and Butylated hydroxytoluene individually mixed with pure Calophyllum inophyllum at concentrations of 200 ppm, 500 ppm and 1000 ppm by weight. The experimental results showed that the addition of antioxidants with Calophyllum inophyllum biodiesel produced higher brake specific fuel consumption and higher brake thermal efficiency compared to pure biodiesel. Significant reductions in oxides of nitrogen emissions were observed with Ethanox and Butylated hydroxytoluene addition with biodiesel at all concentrations compared to neat biodiesel. The reduction oxides of nitrogen emission was 12.6% for Ethanox 1000 ppm and 21% for Butylated hydroxytoluene 500 ppm compared to neat biodiesel. Comparable combustion characteristics were obtained by addition of Ethanox with biodiesel than Butylated hydroxytoluene antioxidant. Moreover, the addition of Ethanox and Butylated hydroxytoluene antioxidants with neat biodiesel increase the carbon monoxide, unburned hydrocarbons and smoke emission at all concentrations than biodiesel. Ethanox addition with biodiesel has shown better results compared to Butylated hydroxytoluene antioxidant.